Republic of Tajikistan : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Modification and Waivers of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2003)
All of the quantitative performance criteria were observed for the period under review. The authorities recognize the numerous challenges facing their program and remain committed to its successful implementation. Given continued strong fiscal performance and the expectation of improved monetary policy implementation, the authorities are confident that they can meet all the program's targets. Discussions with the authorities centered on strengthening the National Bank of Tajikistan (NBT) by restructuring its operations and strengthening the authorities' capacity to implement structural reform.